1980
DOI: 10.1530/jrf.0.0590351
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian cAMP and cGMP fluctuations in the hamster during the oestrous cycle

Abstract: Summary. Cyclic GMP, cAMP and total DNA levels were determined in whole hamster ovaries on each day of the 4-day cycle. Pro-oestrous ovaries were removed during the time of the preovulatory LH surge (confirmed by RIA). Cyclic AMP levels (pmol/mg DNA) were highest during pro-oestrus (1268\m=.\0\ m=+-\139 (s.e.m.)) and lowest during dioestrus 2 (266\m=.\9\ m=+-\22). Cyclic GMP (pmol/mg DNA) levels were highest at dioestrus 2 (87\m=.\2\ m=+-\19) and lowest during oestrus (11\m=.\9\ m=+-\2). Similar patterns were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

1983
1983
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 14 publications
(17 reference statements)
1
12
0
1
Order By: Relevance
“…In the present study, cGMP accumulation was increased by eCG treatment but significantly decreased by the addition of hCG, consistent with previous reports [31]. Previous studies [32,33] have already shown a correlation between the changes in ovarian cGMP and steroid hormones during the hamster estrus cycle. The highest cGMP level, measured in the largest follicles, was observed at 0900 h at the day of proestrus when E 2 was already rising, reaching its peak at 1400 h. This observation is in agreement with our previous report showing that the level of CNP during proestrus was about 4-fold higher than the levels measured at any of the stages of the cycle.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, cGMP accumulation was increased by eCG treatment but significantly decreased by the addition of hCG, consistent with previous reports [31]. Previous studies [32,33] have already shown a correlation between the changes in ovarian cGMP and steroid hormones during the hamster estrus cycle. The highest cGMP level, measured in the largest follicles, was observed at 0900 h at the day of proestrus when E 2 was already rising, reaching its peak at 1400 h. This observation is in agreement with our previous report showing that the level of CNP during proestrus was about 4-fold higher than the levels measured at any of the stages of the cycle.…”
Section: Discussionsupporting
confidence: 93%
“…The high activity of PDE4 in connection with high levels of cAMP suggests that PDE4 is involved in termination of the mid-cycle surge of gonadotropins, which causes a massive cAMP production in the GCs of preovulatory follicles (Hubbard, 1980). In fact, a PDE4 inhibitor in combination with a small dose of hCG has been used to induce ovulation in rats (McKenna et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…As early as 1980, it is found that cGMP levels are highest at dioestrus but lowest during oestrus in hamster ovary [48], suggesting a functional relationship between cGMP levels and meiotic arrest. More and more studies indicate that cGMP is involved in the regulation of oocyte maturation.…”
Section: Cycle Gmpmentioning
confidence: 99%